A multi-hazard framework for coastal vulnerability assessment and climate-change adaptation planning - Yan Zhang; Zhiyun Ouyang; Chao Xu; Tong Wu; Fei Lu (Environmental and Sustainability Indicators, 2024)
When compounded by climate change, ecosystem degradation puts coastal communities at increased vulnerability to hazards. However, there have been few quantitative assessments of coastal vulnerability to multiple hazards that synthesize climate scenarios and ecological and demographic characteristics to inform adaptive strategies. This study presents such a framework for assessing coastal vulnerability to sea level rise, storm waves and winds under present and future climate scenarios. As a case study, we applied it to Macao, one of the most densely populated and highly urbanized coastal area in the world. We found 19% of the coastline hosting 349,000 people – distributed primarily along the Macao Peninsula coast – are highly exposed to coastal hazards at present. Almost half of Macao's total coastline with about 121,000 people are protected by natural habitats. The proportion of highly-exposed coastline was estimated to double, and that of highly-threatened population was estimated to increase by 26.9–44.1%, by 2100. Our findings provide insights into the spatiotemporal heterogeneity of coastal vulnerability to multiple hazards and highlight the role played by habitats in shielding coastal communities. The results can inform prioritizing coastal areas for conservative and adaptive strategies, thereby minimizing deleterious development pressures and enhancing the resilience of coastal communities.